Negative Impact of Thermal Loads on Pressure and Non-Pressure Boiler Parts - Piotr Duda; Łukasz Felkowski (Energies, 2023)
Issues related to the proper design of power boiler elements taking account of thermal loads are still relevant in this era of increasing variability of the boiler power output over time. The aim of this work is to present a thermal and strength analysis for a section of the membrane wall of a steam boiler, designed and manufactured in compliance with international standards, and approved for operation by a pressure equipment supervisory authority. Although the procedures were followed as required, the boiler membrane wall became cyclically damaged. The cause of such periodic damage to the boiler can be explained based on the conducted analyses.